Prevalence of tracheobronchial anomalies among patients undergoing fibreoptic bronchoscopy: a retrospective analysis from a tertiary care hospital in Wayanad, Kerala, India - Sunny, Amitha; Chetambath, Ravindran; Shivashankaran, Sanjeev; Aslam, Muhammed (International Journal of Research in Medical Sciences, 2018)
Background: Tracheobronchial anomalies are a rare clinical entity and often asymptomatic in nature. Some patients may experience symptoms such as cough, recurrent pneumonia or hemoptysis. Knowledge and understanding of tracheobronchial variations have important implications for diagnosis of symptomatic patients and performing certain procedures, including bronchoscopy and endotracheal intubation. Objective was to study the prevalence of tracheobronchial anomalies detected during routine bronchoscopy in a tertiary care setting. Methods: Retrospective analysis of hospital data of patients undergoing fibreoptic bronchoscopy for one year in a tertiary care setting. Results: There were 149 bronchoscopies evaluated. Total of 41 anomalies were detected in 34 (22.8%) subjects. The most common anomaly was bronchial diverticula. Conclusions: This retrospective study takes stock of various tracheobronchial anomalies among subjects who underwent bronchoscopy in a tertiary care hospital in Wayanad, North Malabar. This study revealed major tracheobronchial anomalies in 22.8% of subjects which is higher when compared to previous studies. This is particularly important due to the fact that Wayanad is a backward hilly district and tribal community constitutes 20% of its population.